2022
DOI: 10.1177/02666669221108438
|View full text |Cite
|
Sign up to set email alerts
|

How business intelligence capability impacts decision-making speed, comprehensiveness, and firm performance

Abstract: Scholars and practitioners have trumpeted business intelligence (BI) capability as a game-changer due to its significant impact on firm performance. Despite these claims, the amplifying and underlying mechanisms governing the relationship between BI capability and organizational performance are still in their infancy. This research examines the nexus between BI capability, decision-making speed, comprehensiveness, and organizational performance. This study, drawing on knowledge-based theory, proposes a concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…Drawing from the conclusions of previous studies (Popovi c et al, 2018;Torres et al, 2018;Bo zi c and Dimovski, 2019;Chen and Lin, 2021;Alzghoul et al, 2022) which found a positive significant relationship between BI and firm performance, we expect that BI in SMEs will improve OP. From the above discussion, the first hypothesis has been made.…”
Section: Effect Of Business Intelligence On Operational Performancementioning
confidence: 65%
See 3 more Smart Citations
“…Drawing from the conclusions of previous studies (Popovi c et al, 2018;Torres et al, 2018;Bo zi c and Dimovski, 2019;Chen and Lin, 2021;Alzghoul et al, 2022) which found a positive significant relationship between BI and firm performance, we expect that BI in SMEs will improve OP. From the above discussion, the first hypothesis has been made.…”
Section: Effect Of Business Intelligence On Operational Performancementioning
confidence: 65%
“…Despite the relevance of BI to firms' success, it is still unclear how BI may drive operational performance (OP) among SMEs in emerging economies like Ghana. Amineh et al (2021) also stressed that literature on the implications of BI on SMEs performance is scarce. The few works of literature also produce mixed outcomes on the association between BI and firm performance (Dykes et al, 2019;Shepherd et al, 2020;Amineh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To do this, they must perform at a high level Alzghoul et al, 2022). The ability of the organization to innovate and be creative is reflected in the caliber of the service or product provided (Giannopoulou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%